Differential analysis of mycelial proteins and metabolites from Rigidoporus microporus during in vitro interaction with Hevea brasiliensis Müll.Arg. - Che Fisol, Ahmad Faiz (2021)
Rigidoporus microporus is the fungus accountable for the white root rot disease that is detrimental to the rubber tree, Hevea brasiliensis. The pathogenicity mechanism of R. microporus and the identity of the fungal proteins and metabolites involved during the infection process remains unclear. It was suspected that the changes in R. microporus mycelial protein and metabolite profiles during interaction with the host plant leads to fungal virulence and this study aimed to identify the pathogenicity-related proteins and metabolites of two R. microporus isolates during in vitro interaction with H. brasiliensis. The two R. microporus isolates, Segamat (SEG) and Ayer Molek (AM) were used to inoculate H. brasiliensis clone RRIM 2025 in vitro and the mycelia adhering to the roots of the plant were collected for analysis. Transmission Electron Microscope (TEM) images acquired confirms the hyphae attachment and colonization of the mycelia on the root of the H. brasiliensis clones after four days of inoculation. The protein samples were subjected to 2-DE analysis and analyzed using MALDI-ToF MS/MS while the metabolites were extracted using methanol and analyzed using LC-QToF MS/MS. Based on the differential proteomic and metabolomic analyses, fungal pathogenicity may be the result from protein upregulation that are essential for fungal growth such as malate dehydrogenase, fructose 1,6-biphosphate aldolase (FBA) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and an increase in acidic compounds such as terepthalic acid, mefenamic acid and dihydropteroic acid that led to an increase in cell wall degrading enzyme activity. It can be concluded that the pathogenesis of RM might be related to metabolic pathways (e.g., glycolysis and gluconeogenesis) that involves responsive proteins such as FBA and GAPDH which can be the potential biological markers for early detection of the white root rot disease.